Founder of Hasidism : a quest for the historical Ba'al Shem Tov - Rosman, Murray Jay (Littman library of Jewish civilization (Series), 2014)
"Moshe Rosman supplies the history that proves that the Ba'al Shem Tov, the legendary founder of hasidism, actually existed. He presents the best, most convincing description that can be drawn from the existing documentary evidence, changing our understanding of the Besht and altering the master narrative of hasidism. A substantial new Introduction considers what has changed in the study of hasidism since the influential first edition was published. The Ba'al Shem Tov is an elusive subject for historians because documentary evidence about his life is scanty and equivocal. Until now, much of what was known about him was based on stories compiled more than a generation after his death, many of which serve more to mythologize him than to describe him. The portrait Moshe Rosman provides is drawn from life instead of from myth. Based on innovative critical analysis of both familiar and previously unexplored archival sources, and concentrating on accounts that can be attributed to the Besht or to contemporary eyewitnesses, this book goes further than any previous work in uncovering the historical Ba'al Shem Tov. Additionally, documents in Polish and Hebrew discovered by Professor Rosman during his research for the book enable him to give the first detailed description of the cultural, social, economic, and political context of the Besht's life."--